Finding for new drugs in nature for neglected tropical diseases: in silico study of homolycorine alkaloids against chagas disease - Mora Romero, Daniel (2023)
Chagas disease or American trypanosomiasis is a neglected tropical disease (NTD). It is mainly caused by infection with the Trypanosoma cruzi parasite. In this study, part of an Ibero-American project of a CYTED network devoted to the use of Amaryllidaceae alkaloids as templates for the synthesis of new pharmaceuticals, we have performed a virtual screening of homolycorine-type alkaloids where two alkaloids, 10-Norneronine and 2a,10ba-dihydroxy-9-O-demethylhomolycorine, can be the basis for the design of new drugs due to their interaction with both Trypanothione reductase (TR), and Cruzain (CZ) showing scores close to -7 kcal/mol in molecular docking studies.